A case of fixed asset accounting: Initial and subsequent measurement. (December 2016) - Gissel, Jodi L.
Highlights: Instructional case integrating multiple fixed asset accounting concepts Application of concepts to realistic case beyond textbook exercises and problems Application of accounting knowledge for acquisitions and subsequent accounting Computation of depreciation under various methods Demonstration of critical thinking skills to analyze fixed asset accounting issues Abstract: This instructional case integrates multiple accounting concepts relating to fixed asset acquisition and subsequent measurement. You must apply accounting knowledge, professional judgment, and critical thinking skills to evaluate fixed assets and make recommendations. You must also analyze differences between fixed asset accounting under US generally accepted accounting principles and IFRS. As a student, you generally understand basic application of asset cost computation that simply recognizes the amount of cash paid for acquiring the asset. However, determining asset cost becomes challenging when you encounter more complex situations. You must consider initial measurement issues relating to a land purchase (demolition of existing building and a special assessment expenditure), interest capitalization for a self-constructed building, a nonmonetary asset exchange, and an asset retirement obligation. The case also considers subsequent measurement issues in terms of depreciation (straight-line and accelerated methods), replacement of an asset component, and impairment. The case structure is flexible and the teaching notes include alternatives for using scaled-down versions.